CONSTRUCTION OF KOTA TUA AS CULTURAL HERITAGE AREA ON @KOTATUA.JKT - Sunuantari, Manik; Arianti, Gusmia; Klicek, Tamara; Hasna, Safira (ASPIKOM Jabodetabek Region, 2024)
Kota Tua Jakarta area has become a popular tourist icon of the capital city and has even been nominated as a World Heritage Center by UNESCO. This designation is based on buildings in Kota Tua area that emphasize cultural heritage. Kota Tua Jakarta area is currently managed by the Area Management Unit (UPK) under the Kemenkraf DKI Jakarta. The utilization of Instagram social media is used to promote tourist visits to Kota Tua area.The objective of this research is to understand the construction of meaning of Kota Tua Cultural Heritage and to identify the framing of Kota Tua as a Cultural Heritage Area on @kotatua.jkt Instagram account. The theory used in this research is the construction of reality and framing analysis of Robert Entman, as well as Gamson and Modigliani. The unit of analysis in this research is four Instagram contents that display the Cultural Heritage tourist destinations of Kota Tua Jakarta.The results showed that among the four Cultural Heritage Area contents on Instagram managed by UPK have the historical value of the struggle and the sense of collectiveness of the Batavia community which has now renamed Jakarta. The philosophy of collective cooperation known as “gotong royong”, serves as the fundamental philosophy of Indonesian society. These content represent a strategy employed by UPK to guide the audience’s thinking towards preserving the cultural values of the nation.